Readiness of Malaysian Small and Medium Enterprises (SMEs) Construction Companies for Building Information Modelling (BIM) Implementation - ARIF, NUR KHALIESAH; Hasmori, Muhammad Fikri (Recent Trends in Civil Engineering and Built Environment, 2022)
In terms of the implementation of information technology, the construction sector in Malaysia still lags behind other sectors. Building Information Modelling (BIM) has shown its efficiency in helping the construction industry players. The BIM has thus helped to achieve better integration of project information and to enhance collaboration between stakeholders and the industry players from the early phase of projects. Despite the fact that the technology to implement BIM is readily available and rapidly maturing, the adoption of BIM is still slow. Many governments support adoption of BIM-oriented Integrated Design (ID) approaches on their national markets, however the implementation of BIM software support system among Small and Medium Enterprises (SMEs) in Malaysia is considered inadequate. Hence, the main motivation of this study is to investigate the readiness of Malaysian SMEs construction companies for BIM implementation, evaluate the challenges to implement BIM and develop strategy to overcome the challenges. These aims were accomplished through the online questionnaire survey. The findings of this research have revealed the contemporary barriers and challenges and outlined the adequate strategy to help organisations in the adoption process. This research has confirmed the level of readiness for BIM adoption Malaysian SMEs by analysing scale of knowledge existent. Implementation strategies to overcome these challenges were developed through up-to-date literature review and 109 online questionnaire survey targeted to practitioners in the industry.